Expression Collagen I and III in Anterior Vaginal Women with and without Pelvic Organ Prolapse - Irianta, Trika Irianta (Indonesian Journal of Obstetrics and Gynecology, 2014)
Objective: To find out the expression of collagen I and III in the anterior vaginal wall of women with and without pelvic organ prolapse (POP). Method: The research was a cross sectional study, conducted in Dr. Wahidin Sudiro Husodo hospital and its networks from January 1, 2011 to April 1, 2012. The case group consisted of 35 women with POP level III and IV. The control group consisted of 35 women without POP. The expression of collagen I and III were examined by immunohistochemical test with the staining of antibody of collagen I (mouse monoclonal collagen Iab 90395) and the antibody collagen III (Mu 167 4i). The data was then analyzed by using a computer statistic program with a significance level of 0.05. Result: It was found that in the group of women with POP, there were 28 cases of expression collagen III (84%), which is significantly higher than in women without POP, found in only 20 cases (58.8%), with p=0.02. Meanwhile, in the group of POP, 9.1% of subjects showed moderate expression of collagen I, significantly less compared to the expression in the control group (35.3%), with p=0.007. For the ratio of collagen I and III, the result was weak in women with POP (58.5%) while in the control group, the result was high (85.7%). Conclusion: In terms of collagen I and III expression, there was no significant difference between the two groups. [Indones J Obstet Gynecol 2014; 2: 87-90] Keywords: collagen I, collagen III, pelvic organ prolapse, vaginal wall